Host skin immunity to arthropod vector bites: from mice to humans - Lacsina, Joshua R.; Kissinger, Ryan; Doehl, Johannes S. P.; Disotuar, Maria M.; Petrellis, George; Short, Mara; Lowe, Elliot; Oristian, James; Sonenshine, Daniel; DeSouza-Vieira, Thiago (Frontiers in Tropical Diseases, 2024)
Infections caused by vector-borne pathogens impose a significant burden of morbidity and mortality in a global scale. In their quest for blood, hematophagous arthropods penetrate the host skin and may transmit pathogens by the bite. These pathogens are deposited along with saliva and a complex mixture of vector derived factors. Hematophagous arthopod vectors have evolved a complex array of adaptations to modulate the host immune response at the bite site with the primary goal to improve blood feeding, which have been exploited throughout evolution by these pathogens to enhance infection establishment in the host. While this paradigm has been firmly established in mouse models, comparable data from human studies are scarce. Here we review how the host skin immune response to vector bites in animal models is hijacked by microbes to promote their pathogenesis. We mainly explored four distinct vector-pathogen pairs of global health importance: sand flies and Leishmania parasites, Ixodes scapularis ticks and Borrelia burgdorferi, Aedes aegypti mosquitoes and arboviruses, and Anopheles gambiae mosquitos and Plasmodium parasites. Finally, we outline how critical it is for the field of vector biology to shift from rodent models to clinical studies focused on the interface of vector-pathogen-host immune system to push further the frontiers of knowledge of the field.